Voluntary Disclosure in Indonesia Philanthropy Organizations - Winfiyani, Asifah; Wijayati, Fitri Laela (Profesional Muda Cendekia Publishing, 2023)
The purpose of this paper is to look at the impact of financial and non-financial aspects on voluntary disclosure as a broader form of disclosures. With total of 15 organizations used as samples, obtained from the Indonesia Philanthropy directory in April 2021 by purposive sampling method. The time period used is from 2016 to 2020. The data is then processed using the multivariable regression method. The results of this study showed that the entire variable of the financial aspect had no influence on voluntary disclosure. Non-financial aspects show better outcomes with variables of board size and organization age having a positive impact on voluntary disclosure, while organization size has a negative impact. This research is based on limit sample, so it is not able to describe the actual situation. However the results are still meaningful for the organization, society, and government for making better transparency and accountability.